ETIKA PENGEMBARAAN ILMU MASYARAKAT JAWA PADA NASKAH SERAT DEWA RUCI KARYA R. Ng. YASADIPURA I DALAM PERSPEKTIF KEHIDUPAN MODERN - Suprayitno, Edy (Center of Language and Cultural Studies, 2017)
This research examines the etiques in acquiring knowledge in the Javanese community tradition. The object of this study was Dewa Ruci script by R.Ng. Yasadipura I. The research used qualitative descriptive approach and content analysis as the research design assigning the sociology theory for literature. The finding showed an evidence when acquiring the knowledge, the Javanese always taught four aspects of heritages to their descendants that is inherently asserted in the perspective of the Javanese community and their philosophy. Those aspects attached within the spirit of the Javanese consisted of: (a) enthusiasm, (b) do not give up easily, (c) persistence, and (d) students’ obedience.